Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1111/jaac.12075
|View full text |Cite
|
Sign up to set email alerts
|

Authorship, Co-Authorship, and Multiple Authorship

Abstract: In this article, I use the example of the novel Micro, authored by Michael Crichton and Richard Preston, to tease out the relationships between an author and his work and with other authors of that work. The case presents a complication for a number of contemporary views on authorship and co‐authorship, which suggest that Crichton is either not an author of the novel or an author but not a co‐author—both, I suggest, are counterintuitive views. After working through the leading views on the topic, I present my … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
2
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(1 citation statement)
references
References 3 publications
0
0
0
Order By: Relevance
“…Authorship, co-authorship, and multiple authorship all revolve around issues of power, responsibility, and creation (Hick, 2014). It has been observed that authors who share a kinship tend to hold influential positions within their collaborative networks, as they can leverage their resources (Prosperi et al 2016).…”
Section: Large Number Advantagementioning
confidence: 99%
“…Authorship, co-authorship, and multiple authorship all revolve around issues of power, responsibility, and creation (Hick, 2014). It has been observed that authors who share a kinship tend to hold influential positions within their collaborative networks, as they can leverage their resources (Prosperi et al 2016).…”
Section: Large Number Advantagementioning
confidence: 99%